Length-weight relationship and condition factor of spiny gurnard {lepidotrigla dieuzeidei blanc and hureau, 1973) inhabiting northeast mediterranean sea - Basusta, Asiye; Basusta, Nuri; Calta, Metin; Ozer, Ebru I.; Girgin, Huya (My University, 2013)
The aim of this study was to determine length-weight relationships and to give the maximum length spiny gurnard (Lepidotrigla dieuzeidei Blanc and Hureau, 1973) inhabiting Northeast Mediterranean Sea. A total of 1910 spiny gurnard, (Lepidotrigla dieuzeidei Blanc Hureau, 1973) were obtained from the fishermen on September 2012 to October 2012 in the Northeast Mediterranean Sea. Total length of samples ranged between 7.2-20.4 cm (female), 7.1-17.9 cm (male) and weight 2.28-63.08 g (female), 1.90-47.12 g (male) for L. dieuzeidei, respectively. The length-weight relationships of L. dieuzeidei were found as W = 0.0034 TL335 (R2 = 0.83) for all specimens, W = 0.003TL341 (R2 = 0.84) for females and W = 0.004TL3.28 (R2 = 0.81) for male, respectively. The types of growth for both sexes were positive allometric growth for spiny gurnard. The condition factor values varied between 0.8017 ±0.0057 (female), 0.8076±0.0061 (male) inL. dieuzeidei b-value has been identified as 3.3052, 3.2176, 3.2664, male, female and for all individuals inL. dieuzeidei, respectively. The difference of length-weight relationship between L. dieuzeidei was, statistically insignificant (p>0.05). This study presented the first reference on LWRs and condition factor for spiny gurnard from NE Mediterranean coast of Turkey.
Keywords: Condition factor; Length-weight relationship; Lepidotrigla dieuzeidei; Northeast mediterranean; Spiny gurnard